Online Political Cartoonsâ Pragmatic Analysis and Their Contributions to Efl Studentsâ Pc, Avk and Language Hots - Telaumbanua, Yohannes; Juprizal, Juprizal; Effendi, Mawardi; Mukhiayar, Mukhiayar (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
Political Cartoons (PCs), which have long been media hype, are simple drawings used to send specific critics/messages to the readers. They are, however, often overlooked and even seem to be useless in human life, i.e. in ELT. As a result, they serve as ornaments decorating the walls of the print, electronic, or online mediaâs columns. The messages sent desolately go far away. To linguistically benefit them, the objectives of this mini research were to identify the techniques of analysing PCs and cartoonistâs goals, and explain their contributions to the EFL studentsâ Pragmatic Competence (PC), Authentic Vocabulary Knowledge (AVK), and language Higher-Order Thinking Skills (HOTS). The qualitative paradigm used as a method of searching, collecting, processing, and analysing the data. The subject (respondents/informants) was the PNPâs English department students while the object (source of the data) was the two PCs which were then distributed to be analysed by the students. The library study and documentation were techniques of data collection while interpretational analysis used to analyse the data. The findings are (1) techniques of analysing PCs are Subject, Caption, Action, Message/theme, Symbols (SCAMS); (2) persuasive techniques used to identify the cartoonistâs goals in persuading the readers to think a certain way about a current issue are Symbolism, Exaggeration, Labelling, Analogy And Irony (SELAI). (3) These techniques contributed to enhance studentsâ PC, AVK and HOTS. In conclusion, PCs are media which can be used in enhancing EFL studentsâ PC, AVK and HOTS.